On‐demand field shaping for enhanced magnetic resonance imaging using an ultrathin reconfigurable metasurface. Issue 3 (21st February 2021) - Wang, Hanwei; Huang, Hsuan‐Kai; Chen, Yun‐Sheng; Zhao, Yang
Abstract: The signal‐to‐noise ratio (SNR) is the main figure of merit that assesses the quality of magnetic resonance imaging (MRI). Existing studies mainly focus on improving the magnetic field intensities of the constant homogenous B 0 field from the main coil or the oscillating B 1 field from the radio frequency (RF) coil. In addition to these options, SNR also depends on the coupling between the imaging subject and the RF coil during the signal reception, which has been largely ignored. Here, we provide a different route toward enhancing the SNR of MRI by improving this coupling during the signal reception. We elucidate a theoretical design of an ultrathin metasurface with micrometer thickness and high flexibility. This metasurface is reconfigurable; it can selectively boost the SNR at a desired imaging region with any arbitrary shapes. Our design has shown that this metasurface can enhance SNR by up to 28 times in the region of interest. At the same time, the metasurface is designed to minimally disturb the excitation fields by less than 1.6%, thus maintaining the uniformity of the excitation, important to achieve a high‐quality MR image without artifacts. Abstract : A reconfigurable metasurface is designed to enhance the signal‐to‐noise ratio (SNR) of magnetic resonance imaging (MRI). The metasurface is turned to be off‐resonance during the excitation phase and on‐resonance during the reception phase. The receiving signal from the target region is selective enhanced while the spin‐excitation is minimally disrupted by the metasurface. The brain tumor MR image is reproduced with permission. 19